Exchange rate dynamics and asset price formation - Zarei, Alireza (2015)
Numerous studies on, (i) exchange rate behaviour, and (ii) exchange rate effect on stock prices have led to clear disagreement neither on how exchange rate is determined nor on how exchange rate affects stock prices. Purchasing power parity and interest rate parity theorems offered by monetarist suggest significant influences from inflation and interest rates on exchange rates. The first focus of this study is to investigate how these two factors affect exchange rates by introducing control factors, as suggested in recent studies. Second, empirical support for a significant exchange rate effect on stock returns is also not found, so the next proposition is worth investigating a theory-suggested effect on stock returns from exchange rates. In either case, it is pointed out that the use of more powerful econometric methods is the correct way forward to provide results on these two interesting research problems to explore support for evidence on these propositions. Therefore, this research aims to revisit these two topics using newer methodology and a long-length time series data (over 55 years) from eight major countries. Consensus in the literature is that the two parity theorems are considered puzzles to be resolved by leading researchers. Two eminent scholars have dubbed the lack of support for theories as a “puzzle” as would be detailed in the thesis. Methodological advancements since the early days of research on this topic have shown the following:(i) time series and cross sectional regressions so well entrenched in this line of research actually lead to biased parameter estimation; (ii) panel regression, which is now popular though seldom used by researchers on this topic, is more appropriate and this method has hardly been used; (iii) multi-country panel regressions have been shown to have errors in parameter estimation because of presence of cross sectional dependence, nonstationarity and due to the absence of control on heterogeneity of panel members. Thus, findings in existing literature are likely to change if newer unbiased tests are applied to this research. A number of critical tests (common and mean group estimator, etc.) are conducted so that the panel regression leads to robust measurements.Furthermore, a test on the exchange rate behaviour is conducted for each country to determine the number of structural breaks within the sampled period. Finally, an analysis of cointegration for parity and non-parity variables in the presence of cross-sectional dependence is provided, which is a recently developed advanced procedure. The findings from applying newer methodology are in support of parity and non-parity factors as significant exchange rate relevant factors. Further, it is founded that exchange rate is a significant factor for stock index returns in addition to the relevance of other theory-suggested factors. The final estimators from advanced models applied in this study yield significant test statistics verifying the theory-suggested relationship especially when control factors are included along with corrections for unobserved heterogeneity, serial correlations, nonstationarity and cross sectional dependence (all of which are part of new developments in econometric). It is believed that the efficiency of econometric modelling methodology applied in this research has assisted in providing robust estimation of parameters. This thesis is expected to add useful findings relevant to the monetary economics literature.